1999
DOI: 10.1007/s004180050451
|View full text |Cite
|
Sign up to set email alerts
|

Internalization of amelogenin by dendritic cells of the papillary layer during transition and early maturation stages

Abstract: The existence of amelogenin in the papillary layer facing transition and early maturation zones of ameloblasts of rat incisors and the role of dendritic cells were examined by light microscopic immunocytochemistry and immunoelectron microscopy using anti-porcine 25 kDa amelogenin antibodies and anti-MHC class II antibodies. At the light microscopic level, no overall relationship was observed between anti-class II-positive dendritic cells and anti-amelogenin-positive materials located intercellularly: anti-amel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…Some of the specimens were developed with the AEC substrate kit (DAKO; Carpentia, CA). The sections were further labeled with 1 g/ml Hoechst 33342 (Molecular Probes; Eugene, OR) to detect the transition zone (Nishikawa and Sasaki 1999a) or rhodamine-phalloidin (Molecular Probes) diluted 1:20 with PBS to detect ruffle-ended (RA) or smoothended ameloblasts (SA) (Nishikawa and Josephsen 1987). Procedures for pre-embedding immunoelectron microscopy were described elsewhere (Nishikawa and Sasaki 1999b).…”
Section: Methodsmentioning
confidence: 99%
“…Some of the specimens were developed with the AEC substrate kit (DAKO; Carpentia, CA). The sections were further labeled with 1 g/ml Hoechst 33342 (Molecular Probes; Eugene, OR) to detect the transition zone (Nishikawa and Sasaki 1999a) or rhodamine-phalloidin (Molecular Probes) diluted 1:20 with PBS to detect ruffle-ended (RA) or smoothended ameloblasts (SA) (Nishikawa and Josephsen 1987). Procedures for pre-embedding immunoelectron microscopy were described elsewhere (Nishikawa and Sasaki 1999b).…”
Section: Methodsmentioning
confidence: 99%
“…Proteolytical ECM remodeling not only removes ECM components, but also provides a pro-migratory microenvironment for living cells. In this sense, MMPs play a pivotal role during cell migration (Shapiro 1998), eliciting dendritic cells to phagocyte apoptotic cell fragments and anti-amelogenin-positive material (Nishikawa and Sasaki 1999). We showed that level of immunostaining for MMP-2 and -9 in macrophages and/or in dendritic like cells were highest during the transition phase, decreasing gradually throughout the maturation phase.…”
Section: Discussionmentioning
confidence: 94%
“…It is interesting that dendritic cells beneath the ameloblast layer showed OX6‐immunoreactivity in the developing rat molars. Previous immunohistochemical studies have shown the existence of immunocompetent cells including OX6‐positive cells in the papillary layer during transition and maturation stages of amelogenesis in the rat incisor, a continuously growing tooth (29–31), and suggested the involvement of the class II MHC‐positive cells in the elimination of both enamel proteins such as amelogenin from the enamel organ and apoptotic cell debris (29,31). However, these data were obtained from the rat incisor, not molars.…”
Section: Discussionmentioning
confidence: 99%